Bachelor of landscape architecture thesis : proposed astronomical outdoor gallery at National Planetarium, Kuala Lumpur - Mokhtar, Fahmi; Said, Ismail (2007)
The project presents a design and planning of the outdoor space of the National Planetarium in Kuala Lumpur. The planetarium exhibits equipment and artefacts on astronomy and space technology to travel beyond the Earthâ€™s atmosphere. This indoor gallery allows people to observe the celestial objects and learn about phenomena in space. But the indoor spaces in the building limit the activities to educate people. Therefore, this proposal intends to extend the learning process of astronomy to the outdoor as a gallery. The 23-acre gallery is located on a hilltop of hill that affords scenic view to the city. The concept of the design is â€œevolution of astronomical time-lineâ€ which highlights a journey from ancient period to modern technological era. The site is divided into eight zones: Ancient Period, Mesopotamian, Egyptian, Early Greek, Chinese, Islamic, Renaissance and Modern Era which is famous for their exploration of celestial objects. Firstly, the ancient park let visitors to experience the early astronomical era from 3100B.C. such as the Stonehenge and Babylonian astronomy. Facilities such as information centre, food corner, surau, phone booth and toilet are provided. The rest of the zones are composed instruments and sculptures such as astrolabe, globe, quadrant, sundial and equatorium to highlight the character of the era and automatically become a landmark to generate emotional attachment among users. Finally, the journey of the time-line ends at Modern Era Park where visitors can interact with the exhibition items in observatory gallery, playing with the water element and small kiosk and observe the celestial objects. Children also can learn about astronomy while they are playing with the sun tunnels and other equipments in children planet. The users can experience about the evolution of astronomy after they complete their journey in all zones.